Reversible regulation of SATB1 ubiquitination by USP47 and SMURF2 mediates colon cancer cell proliferation and tumor progression. (28th April 2019) - Yu, Le; Dong, Ling; Wang, Yang; Liu, Liu; Long, Hua; Li, Hui; Li, Jinping; Yang, Xiaolong; Liu, Zhaojian; Duan, Guangjie; Dai, Xiaotian; Lin, Zhenghong
Abstract: Upregulation of special AT-rich sequence-binding protein-1 (SATB1) has been suggested to promote tumor growth and metastasis. However, the factors governing its cellular levels remain unclear. Here, we report that ubiquitin-specific peptidase 47 (USP47), a member of the deubiquitinating enzymes family, interacts with SATB1 and mediates its deubiquitination and stability. USP47 deficiency impairs transcriptional activity of SATB1 target genes and inhibits colon cancer cell proliferation, migration, and tumorigenesis in a mouse model of colon cancer. Furthermore, we identified SMURF2 as an E3 ubiquitin ligase that promotes SATB1 degradation by upregulating its ubiquitination, and its deficiency promotes colon cancer cell proliferation and SATB1 target gene transcription. SMURF2 is negatively regulated by USP47, and USP47 depletion sensitizes colon cancer cells to 5-FU treatment-induced apoptosis. Taken together, our findings provide a ubiquitination-related mechanistic link to USP47, SMURF2, and SATB1 and suggest that USP47 might be targeted for colon cancer treatment when SATB1 is overexpressed. Highlights: SATB1, a tumor-promoting factor in colorectal cancer (CRC), was identified as a substrate of deubiquitinase USP47. USP47 promotes colon cancer cell growth and migration through SATB1. USP47 reprograms the expression profiles of cell growth and tumor metastasis-related genes. SMURF2 is an E3 ubiquitin ligase of SATB1 that promotes its proteasome-mediated degradation. USP47/SATB1 depletion sensitizes colon cancer cells to apoptosis.